Zerlegen und Zusammensetzen: Fähigkeiten von Vorschulkindern beim Umstrukturieren von Bauwerken unter Berücksichtigung von Teil-Ganzes-Beziehungen (mathematica didactica, 2013)
Spatial structuring includes mental splitting of a composition into components and composing components to new units. Structures can be decomposed and flexibly restructured again. For analyzing individual (re-)structuring processes, a diagnostic model is proposed including geometric and arithmetic ability aspects. With this, preschooler’s abilities to restructure concrete buildings are analyzed. The development of spatial structuring abilities is investigated while comparing strategies before and after a mathematical intervention. Results show, that preschooler’s prevalent form of disintegrating a given structure is to mentally divide each given unit into new ones. However, creating superior composite units requires a consideration of global relations. Besides, getting aware of compositions is an advantage in the development of the numerical concept of part-whole-relationships.